2014
DOI: 10.1111/ajt.12909
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and the Development of Posttransplant Chronic Lung Allograft Dysfunction

Abstract: Chronic lung allograft dysfunction (CLAD) is the leading cause of mortality following lung transplantation. We conducted a retrospective cohort study including 397 bilateral lung recipients transplanted in from 1996 to 2009 to determine the association between ambient air pollution, CLAD and mortality. Pollution exposure was assessed using satellite‐based estimates of nitrogen dioxide, distance to major roadway and total length of roadways around a patient's home. Cumulative exposures to ozone and particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 43 publications
3
29
1
1
Order By: Relevance
“…Many studies have shown associations between pollution exposure and the incidence and/or progression of multiple pulmonary diseases, including asthma, 1 COPD, 2 bronchiectasis, 3 respiratory infections, 4 chronic lung allograft dysfunction 5 and lung cancer. 6 There has been little research on whether air pollution may contribute to the etiology or accelerate the progression of interstitial lung diseases (ILDs), a heterogeneous group of chronic lung diseases characterized by inflammation and fibrosis of the pulmonary parenchyma that affect nearly 1 out of 200 older adults in the U.S. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown associations between pollution exposure and the incidence and/or progression of multiple pulmonary diseases, including asthma, 1 COPD, 2 bronchiectasis, 3 respiratory infections, 4 chronic lung allograft dysfunction 5 and lung cancer. 6 There has been little research on whether air pollution may contribute to the etiology or accelerate the progression of interstitial lung diseases (ILDs), a heterogeneous group of chronic lung diseases characterized by inflammation and fibrosis of the pulmonary parenchyma that affect nearly 1 out of 200 older adults in the U.S. 7 …”
Section: Introductionmentioning
confidence: 99%
“…For each 10‐fold increase in distance from major roads, hazard ratios and mortality went down for these patients . These findings have since been replicated .…”
Section: Bos As a Model For Chronic Rejectionmentioning
confidence: 65%
“…Few studies have estimated the impact of chronic exposure to ambient air pollutants in lung transplant recipients (LTRs), a population with a potential higher sensitivity to air pollution exposure due to cumulative effects of ischaemic reperfusion insult and innate and adaptive immune activation. Two previous studies have indicated that traffic-related air pollution, assessed with proximity to major road, was associated with the risk of development of CLAD, bronchiolitis obliterans syndromes (BOS) and of mortality after lung transplantation [14,15]. The Canadian study did not detect any significant association between CLAD occurrence and mean annual concentrations of particulate matter with an aerodynamic cut-off of 2.5 µm (PM2.5), ozone (O 3 ) and nitrogen dioxide (NO 2 ) estimated at the residential address using nearby fixed-site monitoring stations [14].…”
Section: Introductionmentioning
confidence: 99%